EFFECTS OF TYPES OF MEDIA AND NPK FERTILIZER ON THE ROOTING CAPACITY OF CHRYSANTHEMUM CUTTINGS - K. Budiarto; Y. Sulyo; E. Dwi S.N.; R.H.M. Maaswinkel (Indonesian Agency for Agricultural Research and Development, 2006)
Physiological status of chrysanthemum cuttings during rooting process highly influences plant growth and flower production. Amongst other aspects, rooting capacity of the cuttings is the most important. Rooting capacity is influenced by environmental conditions such as growing medium and nutrition. The study was aimed to analyze the effects of different types of media, fertilizer concentration, and frequency of fertilizer application on the rooting capacity of chrysanthemum cuttings. The experiment was conducted at the Segunung Experimental Station of the Indonesian Ornamental Crops Research Institute from February to May 2005. The treatments consisted of four different rooting media, i.e. carbonized rice husk, coco peat, perlite, and mixture of perlite and vermiculite (1:1 v/v); two concentrations of NPK (25:7:7) fertilizers, i.e. 1.75 and 2.5 g 1-l; and four frequencies of fertilizer application, i.e. every 1 day, 2 days, 3 days, and 4 days. The experiment was designed in a completely randomized block with four replications. Parameters observed were rooting capacity and cutting performances such as cutting height, cutting diameter, number of leaves, number of visible roots, and root length at 16 days after planting. The results showed that chrysanthemum cuttings rooted in carbonized rice husk had better performance than those rooted in coco peat, vermiculite, and mixture of perlite + vermiculite. Higher concentration of fertilizer solution up to 2.5 g l-1 also gave significant effect on the root formation and further root growth of cuttings. However, the rooting capacity of cuttings was not affected by the frequency of fertilizer application. This study implied that carbonized rice husk growing medium supplemented with NPK (2.5 g l-l) every 4 days during rooting period is the choice for traditional chrysanthemum growers to increase the perform-ance and quality of the cut flowers.